Effect of IV High-Dose Vitamin C on Mortality in Patients With Sepsis: A Systematic Review and Meta-Analysis of Randomized Controlled Trials*. Issue 12 (8th September 2021) - Sato, Ryota; Hasegawa, Daisuke; Prasitlumkum, Narut; Ueoka, Miki; Nishida, Kazuki; Takahashi, Kunihiko; Nasu, Michitaka; Dugar, Siddharth
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: The aim of this study was to conduct a systematic review and meta-analysis of randomized controlled trials to investigate whether IV high-dose vitamin C improves the short-term mortality of patients with sepsis. DESIGN: This study is a systematic review and meta-analysis of randomized controlled trials. We searched EMBASE, the Cochrane Central Register of Controlled Trials, and MEDLINE for randomized controlled trials that met inclusion criteria. The protocol was registered at the University hospital Medical Information Network Clinical Trials Registry (UMIN000040528). All analyses were presented with the use of random-effects models. The primary outcome was short-term mortality defined as 28-day, 30-day, or in-hospital mortality. PATIENTS: Two authors independently evaluated the following eligibility criteria: 1) randomized controlled trial, 2) patients with sepsis aged ≥18 years, and 3) received intravenous high-dose vitamin C in addition to standard of care, or standard of care alone. Then, two authors independently extracted the selected patient and study characteristics and outcomes from studies that met above eligibility criteria. MEASUREMENTS AND MAIN RESULTS: Eleven randomized controlled trials ( n = 1, 737 patients) were included in this meta-analysis. High-dose IV vitamin C was not associated with a significantly lower short-term mortality (risk ratio, 0.88; 95% CI, 0.73–1.06; p = 0.18; I 2 = 29%) but was associated with a significantly shorter duration of vasopressor use (standardized mean difference, –0.35; 95% CI, –0.63 to –0.07; p < 0.01; I 2 = 80%) and a significantly greater decline in the Sequential Organ Failure Assessment score at 72–96 hours (standardized mean difference, –0.20; 95% CI, –0.32 to –0.08; p < 0.01; I 2 = 16%). One study reported significant association with hypernatremia, but adverse effects were rare, and high-dose vitamin C is deemed relatively safe. CONCLUSIONS: In this meta-analysis, the use of IV high-dose vitamin C in patients with sepsis was not associated with lower short-term mortality although it was associated with significantly shorter duration of vasopressor use and greater decline in the Sequential Organ Failure Assessment score at 72–96 hours.